(untitled) (Journal on studies and research of academic knowledge, 2010)
From the investigation lineament “University Teaching: developing skills and teaching strategies”, is addressed in particular the way teachers teach and how students learn in the UNI, answering questions about the characteristics of T-L process, teaching resources used, concept of “learning” and educational paradigms that involve teaching. It aims to achieve the research objectives in order to obtain a diagnosis Of the current situation of the institution regarding the variables analyzed. The level of research is exploratory and descriptive, a mixed approach. The universe is composed of faculty members and students of UNI. The instruments were applied to 252 units of analysis in a population of 3,381. The sample provides 90% accuracy with 5% sampling error. The collection of data and information is performed during the months of June, July and August 2010 in the different academic units of the National University of Itapúa, Encarnación, Paraguay. The research results allow us to infer that the relevant characteristics of the T–L process are related to personal attitudes of professors, knowledge owned by them, knowledge of the objectives and usefulness of each item developed, that the type of teaching and learning strategies implemented favor knowledge processes and it is necessary to strengthen the structural organization of classes and highlights the awareness of students in that self-motivation is “their” responsibility. The teaching resources used in the development of classes contribute positively to their learning. Teaching practices are part of the educational paradigms that enable students to construct their learning, ponder over it and socialize.